2018
DOI: 10.1007/s00586-018-5778-7
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and the intervertebral disc: a biochemical link exists between obesity, intervertebral disc degeneration and low back pain—an in vitro study in a bovine model

Abstract: The aim of this study was to identify the effects of leptin upon the intervertebral disc (IVD) and to determine whether these responses are potentiated within an environment of existing degeneration. Obesity is a significant risk factor for low back pain (LBP) and IVD degeneration. Adipokines, such as leptin, are novel cytokines produced primarily by adipose tissue and have been implicated in degradative and inflammatory processes. Obese individuals are known to have higher concentrations of serum leptin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 61 publications
1
43
0
1
Order By: Relevance
“…However, there are some contradictory data reporting that cumulative or repetitive loading associated with higher body mass have no deleterious action on IVD [29]. This suggests that beyond mechanical effects, obesity could exert metabolic and/or inflammatory effects that contribute to IVDD development [30,31].…”
Section: Ivdd and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some contradictory data reporting that cumulative or repetitive loading associated with higher body mass have no deleterious action on IVD [29]. This suggests that beyond mechanical effects, obesity could exert metabolic and/or inflammatory effects that contribute to IVDD development [30,31].…”
Section: Ivdd and Obesitymentioning
confidence: 99%
“…Analyzing the effects of leptin in disc cells proteome, recently, Segar and colleagues demonstrated that this adipokine, alone or in synergy with TNF-α, IL-1β, or IL-6, significantly increases nitric oxide production, and the expression of pro-inflammatory cytokines (TNF-α and IL-6), and MMPs (MMP-3, -7, -9, and -11, as well as ADAMTS -4, and -5) [31]. These data indicated that leptin can initiate degradative and inflammatory cascades in disc cells, being its deleterious effects potentiated by an existing inflammatory environment [31]. Similar effects were previously verified by Miao et al in rat NP cells [40].…”
Section: Adipokines In Ivddmentioning
confidence: 99%
“…However, adipokines have been reported to play major roles in the systemic diseases [15][16][17], including arthritis, and disc degeneration, known as the most common orthopedic disease [18][19][20][21]. According to data, leptin and resistin accelerated disc degeneration by inducing inflammation, and then substrate degradation [22][23][24]. No study has reported about the role of chemerin in intervertebral disc, so the objective of our study was to explore the relationship between chemerin, intervertebral disc, inflammation, and matrix degradation.…”
Section: Agingmentioning
confidence: 99%
“…It was shown that the addition of leptin can initiate and potentiate (when combined with TNF-α, IL-1β, or IL-6) the production of molecules involved in IVD degeneration and back pain, namely, MMPs and NO. [110] As described for articular cartilage in the previous section, one of the current trends in regenerative medicine, in vitro, is the use of decellularized matrices as 3D support material. This native tissue provides the unique ECM composition and Biomaterial-based culture HMw-HA hydrogels with NP cells HA hydrogel suppressed the expression of the inflammatory receptors IL-1R1 and My D88 and downregulated the expression of NGF and BDNF.…”
Section: In Vitro Models-inflammatory Players and Ivd Cellsmentioning
confidence: 99%